Rancang Bangun Sistem Informasi Rental Mobil Berbasis Web Terintegrasi WhatsApp Chatbot CV Domia Group - Flavius Pratama Putra; Deni Risdiansyah; Erni (LKP KARYA PRIMA KURSUS, 2026)
Abstract The development of information technology has brought fundamental changes to various industrial sectors, including the vehicle rental business. CV Domia Group still faces operational problems in managing vehicle data, consumer data, rental transactions, and information services that are still carried out conventionally. This study aims to design and implement a Web-Based Car Rental Information System integrated with WhatsApp Chatbot as a means of automatic vehicle booking. The system development method applied is the Waterfall model with the stages of needs analysis, design, implementation, testing, and maintenance. The system was built using the PHP programming language with the CodeIgniter 3 framework and MySQL database, and integrated with WhatsApp Chatbot through the SunWa Application Programming Interface to automate information services and vehicle bookings. Test results using the Black Box Testing method show that all system functionality runs according to user needs. The developed system is proven to optimize the integrated management of car rental operational data, shorten the vehicle booking process, and improve the effectiveness of service to CV Domia Group Sanggau customers.